Observation of the ionosphere by ionosondes in the Southern and Northern hemispheres during geospace events in October 2021 - Reznychenko, M.; Bogomaz, O.; Kotov, D.; Zhivolup, T.; Koloskov, O.; Lisachenko, V. (Ukrainian Antarctic Journal, 2022)
The paper presents the results of ionospheric observations performed over the Ukrainian Antarctic Akademik Vernadsky station and Millstone Hill (USA). Ionospheric parameters such as peak electron density and height (hmF2 and NmF2) in October 2021 are shown and discussed. The results of the comparative analysis between observations and predictions of the International Reference Ionosphere 2016 (IRI-2016) model are presented. The main objectives of this work are an investigation of the ionosphere response to space weather effects in the Northern and Southern hemispheres in the American longitudinal sector using ionosondes located at the Vernadsky station and near the magnetically conjugate region – Millstone Hill, and a comparison of observations with the model. The F2-layer peak height was calculated from ionograms obtained by ionosonde using subsequent electron density profile inversion. Diurnal variations of hmF2 and NmF2 were calculated using a set of sub-models of the IRI-2016 model for comparison with experimental results. A strong negative response of the ionosphere to the moderate geomagnetic storm on October 12, 2021 was revealed over the Vernadsky station and Millstone Hill. During October 21–31, 2021, the gradual night-to-night increase in NmF2 (by a factor of 2) was observed over the Vernadsky station. It was found that the IRI hmF2 sub-models (SHU-2015 and AMTB-2013) provide a relatively good agreement with the observed variations of hmF2 in the daytime and nighttime for almost the entire investigated period over both the Vernadsky station and Millstone Hill. The largest deviations for both IRI hmF2 sub-models occurred during the nighttime of geomagnetically disturbed periods. The IRI NmF2 submodels (URSI and CCIR) generally agree with the observations. However, observations and model predictions differ somewhat in the geomagnetically disturbed periods. According to the results of the standard deviation calculations, it cannot be concluded that any of the IRI-2016 sub-models is better than the others. The hypotheses on the possible reasons for the differences in the modeled and observed variations of hmF2 and NmF2 are proposed and discussed in the frame of well-known ionospheric storms’ mechanisms. The results obtained in this paper demonstrate the peculiarities of the ionosphere in different hemispheres of the American longitude sector under geomagnetically quiet and disturbed conditions and provide one more validation of the modern empirical international reference models of the ionosphere.